A new approach to assess safety performance of rail regions with an emphasis on the resources and equipment of each region. (March 2023) - Bondarabadi, Moslem Azizi; Rahimi, Hamid; Arefkhani, Hessam; Kashani, Ali Tavakoli
Abstract: Providing a comprehensive overview of the safety status of similar large-scale rail spatial units (such as existing Rail Regions (RRs) in a country) is a first but very important step in identifying policies that can accelerate progress in improving rail safety. The aim of the current study is to present a new approach to assess RR's safety performance with an emphasis on the Resources and Equipment (R&E) of each RR. To reach the study goal, first, a conceptual framework is developed to make a relationship among exposure, safety, and R&E of RRs. In the next step, Data Envelopment Analysis (DEA) model with Fuzzy-Delphi method is used to evaluate the safety performance of different RRs. In this evaluation, the data regarding safety status of 20 RRs of Iran in 2020 are used. Results showed that Region #1 has the best safety efficiency and Northeast Region #20 has the lowest safety efficiency among other regions. It was also revealed how much of each RR's resources (e.g. track repairmen and maintenance crews, etc.) are using inefficiently. Moreover, some suggestions for improving safety performance of each region were also presented based on the amount of resources using inefficiently. By considering R&E of each region in the proposed approach, a more impartial comparison can be made on the RR's safety performance. Therefore, the decision maker could have a more realistic and fairer view of the safety status of different RRs. Finally, it is worth mentioning that previous studies generally aimed at assessing RRs' safety based on their safety level without involving R&E of each RR. However, it seems an incomplete assessment considering the fact that different RRs have different amount of R&E. Thus, the current study is trying to fill this gap by taking into account R&E of each RR. Highlights: Providing a comprehensive overview of the safety status of similar large-scale rail spatial units (such as RRs in a country) is a first but very important step in identifying policies that can accelerate progress in improving safety. The aim of the current research is to evaluate the rail safety performance of RRs in a fair environment (i.e. taking into account R&E of each region in improving safety). For a more realistic and fairer comparison R&E of each RR should be also considered and associated factors to exposure, lack of safety, and R&E have to be identified. To evaluate rail safety performance of RRs, a Data Envelopment Analysis (DEA) model is used. We define "reference region" for a RR as a region that is most similar to that RR in terms of resources and safety equipment but with a better efficiency.